2019
DOI: 10.1002/prs.12087
|View full text |Cite
|
Sign up to set email alerts
|

An integrated method for quantifying and managing extreme weather risks and liabilities for industrial infrastructure and operations

Abstract: The physical forces and environmental stressors that occur during extreme weather events place facilities at risk for infrastructure failures, loss of operation and production, and highly impactful chemical releases, all of which directly affect a company's bottom line. Hurricane Harvey (2017) resulted in over 100 such failures and chemical releases. There is a pressing need today for risk predictions that incorporate and account for evolving environmental factors such as continuous sea level rise. Such nonsta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The increasingly volatile weather in Australia and the extreme events already impacting firms in the form of bushfires, floods, drought, and hailstorms may enhance the focus of firms on physical risk [57][58][59][60]. Firms have been aware of physical risks from weather and climate for longer than they have been focusing on transitional risks, as these risks can be more easily assessed by analysing historical records [61].…”
Section: Supervised Classificationmentioning
confidence: 99%
“…The increasingly volatile weather in Australia and the extreme events already impacting firms in the form of bushfires, floods, drought, and hailstorms may enhance the focus of firms on physical risk [57][58][59][60]. Firms have been aware of physical risks from weather and climate for longer than they have been focusing on transitional risks, as these risks can be more easily assessed by analysing historical records [61].…”
Section: Supervised Classificationmentioning
confidence: 99%
“…Their study highlighted the importance of sharing information related to chemical hazards, accident risks, and first response procedures within a company, the local government, and the public, before and during natural disasters 9 ; risk assessments were also performed and standardized methods were developed to precisely analyze Natech risks such as earthquakes, floods, gale-winds, lightning, and wildfire. [10][11][12][13][14][15][16][17] Countermeasures and preventive procedures against Natech risks were also investigated for adequate risk management and mitigation. The safety triad, which is a concept developed by Prof. Mannan, was applied to prepare for climate extremes affecting chemical industries, and it was effective in identifying deficiencies in safety systems.…”
Section: Introductionmentioning
confidence: 99%
“…Araki et al reported on the damage and evacuation activities caused by the flood‐induced explosions at an aluminum plant in Japan in 2018. Their study highlighted the importance of sharing information related to chemical hazards, accident risks, and first response procedures within a company, the local government, and the public, before and during natural disasters 9 ; risk assessments were also performed and standardized methods were developed to precisely analyze Natech risks such as earthquakes, floods, gale‐winds, lightning, and wildfire 10–17 . Countermeasures and preventive procedures against Natech risks were also investigated for adequate risk management and mitigation.…”
Section: Introductionmentioning
confidence: 99%